1996
DOI: 10.1093/jaoac/79.4.902
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination of Tocopherols and Tocotrienols in Margarine, Infant Foods, and Vegetables

Abstract: A liquid chromatographic (LC) method was developed for determination of tocopherols and tocotrienols in foods. Tocopherols and tocotrienols were released after saponification of test portions for 40 min at 80°C, followed by extraction with hexane-ethyl acetate. After evaporation of the organic solvents, the extract was injected into the LC system. Separation of individual tocopherols and tocotrienols was satisfactory. Some interferences were encountered from tocomoneols, tocodienols, 2-tert-butyl-4-hydroxyanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…In recent years, HPLC has overtaken GC as the method of choice for vitamin E determination because of the greater flexibility and convenience it offers in handling different sample matrices 2. For routine determination of vitamin E in foods and tissues, the normal procedure is first to liberate the vitamin from the sample matrix by saponification 126–130. Saponification procedures require prolonged heating of the sample in aqueous potassium hydroxide at elevated temperatures, usually 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, HPLC has overtaken GC as the method of choice for vitamin E determination because of the greater flexibility and convenience it offers in handling different sample matrices 2. For routine determination of vitamin E in foods and tissues, the normal procedure is first to liberate the vitamin from the sample matrix by saponification 126–130. Saponification procedures require prolonged heating of the sample in aqueous potassium hydroxide at elevated temperatures, usually 70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The methods detailed in [35,36,37,38] were followed to assess the contents of ascorbic acid (AsA), glutathione (GSH), and α-tocopherol (α-TOC).…”
Section: Determination Of Non-enzymatic Antioxidants Contentsmentioning
confidence: 99%
“…Vitamin E is composed of a number of tocopherol analogues ( α ‐, β ‐, γ ‐, δ ‐) and their corresponding unsaturated tocotrienols. Clinical interest in antioxidant micronutrients, such as vitamin E, in several degenerative human health conditions12 and retinol deficiency as well as their relationship with abnormal retinoids metabolism, which is associated in neural degeneration with ageing and certain brain pathologies such as Alzheimer's diseases,13, 14 has been growing in recent years. Recent epidemiological and clinical studies have suggested that fat‐soluble vitamins A and E protect against coronary heart disease and that they may play a key role in the prevention of some cancers 15–17.…”
mentioning
confidence: 99%